A 3D DLM/FD method for simulating the motion of spheres in a bounded shear flow of Oldroyd-B fluids. (30th August 2018) - Chiu, Shang-Huan; Pan, Tsorng-Whay; Glowinski, Roland
Highlights: Present a novel DLM/FD method for simulating ball interaction in an Oldroyd B fluid. Two ball interactions in a shear flow are studied for Weissenberg numbers up to 1. A tumbling two ball chain can be formed, depending on the ball initial position. Kayaking motion may occur, depending on the value of Weissenberg number. Abstract: We present a novel distributed Lagrange multiplier/fictitious domain (DLM/FD) method for simulating fluid-particle interaction in Oldroyd-B fluids under creeping conditions. The results concerning two ball interaction in a three dimensional (3D) bounded shear flow are obtained for Weissenberg numbers up to 1. The pass and return trajectories of the two ball mass centers are similar to those in a Newtonian fluid; but they lose the symmetry due to the effect of elastic force arising from viscoelastic fluids. A tumbling chain of two balls (a dipole) may occur, depending on the value of the Weissenberg number and the initial vertical displacement of the ball mass center to the middle plane between two walls.